The Influence of Intra-School Student Organizations (OSIS) on the Formation of Pancasila Student Profiles at SMKN 3 Pekanbaru - M. Rizky Edriansyah; Sri Erlinda; Indra Primahardani (Journal of Education Technology Information Social Sciences and Health, 2024)
This research is motivated by the independence curriculum, one of the achievements of which is the Pancasila Student Profile, which aims for Indonesian education to embody Indonesian students as students who have global competence and have behavior that is in accordance with Pancasila values. We certainly don't get the formation of the Pancasila Student Profile from the learning process alone, there are organizations that facilitate the implementation of the formation of the Pancasila Student Profile. The activities of the school and OSIS are able to have a positive impact, making it easier to understand the Pancasila Student Profile. The aim of this research is to determine the influence of OSIS on the formation of the Pancasila Student Profile at SMKN 3 Pekanbaru, using descriptive quantitative research. Meanwhile, data collection techniques use questionnaires, documentation and interviews. The results of the F test obtained that F_tab is 4.052 while F_hit is 43.798 so it can be concluded that in this case F_hit is greater than F_tab so Ho is rejected and so Ha is accepted. Based on this statement, this research hypothesis is accepted. The relationship between OSIS and the formation of the Pancasila profile is in the strong range. Where the value of the relationship (R) is 0.698. From this output, a coefficient of determination (R Square) of 0.488 was obtained, which means that the influence of the independent variable (OSIS) on the dependent variable (Pancasila Student Profile) was 48.8%. so it can be concluded that the Intra-School Student Organization has a positive influence on the Pancasila Student Profile at SMKN 3 Pekanbaru.